Recent Advances in the Synthesis of Organic Thiocyano (SCN) and Selenocyano (SeCN) Compounds, Their Chemical Transformations and Bioactivity - Rodrigo Abonia; Daniel Insuasty; Juan-Carlos Castillo; Kenneth K. Laali (Molecules)
New approaches for the synthesis of organic thio- and selenocyanates, and methods to incorporate them into more complex structures, including a wide variety of heterocyclic and polycylic derivatives, are reviewed. Protocols that convert the SCN and SeCN moieties into the thio and seleno derivatives by transforming the cyano group are also examined. In representative cases, the bioactivity data for these classes of compounds are reviewed.